2010
DOI: 10.1242/dmm.003012
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of metaplastic Barrett’s epithelium into post-mitotic goblet cells by γ-secretase inhibition

Abstract: SUMMARYBarrett's esophagus (BE) affects approximately 2% of the Western population and progresses to esophageal adenocarcinoma (EAC) in 0.5% of these patients each year. In BE, the stratified epithelium is replaced by an intestinal-type epithelium owing to chronic gastroduodenal reflux. Since selfrenewal of intestinal crypts is driven by Notch signaling, we investigated whether this pathway was active in the proliferative crypts of BE. Immunohistochemistry confirmed the presence of an intact and activated Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…To our knowledge, direct nongoblet-to-goblet transition has not been demonstrated in esophageal epithelium in vitro. In vivo, treatment with γ-secretase inhibitors and resultant loss of Notch signaling in a surgical rat model of reflux esophagitis and Barrett's metaplasia leads to esophageal goblet cell hyperplasia within the reflux-induced metaplasia (58). During mouse esophageal development, hypomorphic SOX2 or complete loss of expression of either p63 or Noggin causes the appearance of goblet-like cells within the epithelium (53,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, direct nongoblet-to-goblet transition has not been demonstrated in esophageal epithelium in vitro. In vivo, treatment with γ-secretase inhibitors and resultant loss of Notch signaling in a surgical rat model of reflux esophagitis and Barrett's metaplasia leads to esophageal goblet cell hyperplasia within the reflux-induced metaplasia (58). During mouse esophageal development, hypomorphic SOX2 or complete loss of expression of either p63 or Noggin causes the appearance of goblet-like cells within the epithelium (53,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…In the esophagus, Notch signaling has also been reported to be important for esophageal epithelial homeostasis, 9 as well as for the development of BE 10,11 and Barrett's adenocarcinoma. 12 In addition, we recently reported that activation of ATOH1 via Hes1 suppression in esophageal epithelial cells due to induction of Cdx2 expression in response to bile acids has important functions in induction of metaplastic changes during BE development.…”
mentioning
confidence: 99%
“…Indeed two recent studies independently identified small molecules that suppress activating mutations in the Wnt pathway by stabilizing Axin, an endogenous repressor of the Wnt pathway [39,40]. Likewise a class of inhibitors of the Notch pathway called gamma-secretase inhibitors have been shown to effectively block stem cell maintenance and to force the differentiation of progenitor cells in murine models of intestinal adenoma [38] and a related cancer, metaplastic Barrett's esophagus [41].…”
Section: Models To Identify Anti-csc Drugs For Crcmentioning
confidence: 99%